Stochastic modeling of the thermal and catalytic degradation of polyethylene using simultaneous DSC/TG analysis - Trindade, Nuno Miguel Passarinho (2013)
Dissertação para obtenção do Grau de Mestre em Engenharia Química e Bioquímica